Experimental and numerical investigation of the aerodynamic interactions between a hovering helicopter and surrounding obstacles - Gallas, Q.; Boisard, R.; Monnier, J.-C.; Pruvost, J.; Gilliot, A. (My University, 2017)
This paper presents the work carried out by the Aerodynamics Aeroelasticity and Acoustics Department of ONERA in the framework of the GARTEUR (Group for Aeronautical Research and Technology in Europe) Action Group 22 “Forces on Obstacles in Rotor Wake”. The ONERA activities consist in two tasks performed in parallel, both presented in this paper. It first consists in an original experimental activity to study the aerodynamic interactions of a helicopter model placed in a square pit. The objective of this test campaign is to experimentally characterize the aerodynamic interactions between a helicopter and its surrounding. Experimental measurements include aerodynamic forces, wall static pressures, flow visualizations and Stereo-PIV in the field. The results help in the understanding of the complex flow phenomena encountered. Then since the boundary conditions of the experiment are well documented, the experimental database allows the validation of numerical tools, which is the second task presented in this paper. The objective of the numerical study is to validate the ONERA low fidelity tool PUMA by comparing its aerodynamic rotor loads prediction to the different available databases. PUMA tool is based on a lifting line approach coupled with a freewake model. The results show good agreement between the numerical findings and the experimental results and prove the ability of the PUMA tool to accurately simulate such a complex flow interaction mechanism.